Bi-allelic truncating mutations in VWA1 cause neuromyopathy - Deschauer, Marcus; Hengel, Holger; Rupprich, Katrin; Kreiß, Martina; Schlotter-Weigel, Beate; Grimmel, Mona; Admard, Jakob; Schneider, Ilka; Alhaddad, Bader; Gazou, Anastasia; Sturm, Marc; Vorgerd, Matthias; et al. (Brain, 2021)
The von Willebrand Factor A domain containing 1 protein, encoded by VWA1, is an extracellular matrix protein expressed in muscle and peripheral nerve. It interacts with collagen VI and perlecan, two proteins that are affected in hereditary neuromuscular disorders. Lack of VWA1 is known to compromise peripheral nerves in a Vwa1 knock-out mouse model. Exome sequencing led us to identify bi-allelic loss of function variants in VWA1 as the molecular cause underlying a so far genetically undefined neuromuscular disorder. We detected six different truncating variants in 15 affected individuals from six families of German, Arabic, and Roma descent. Disease manifested in childhood or adulthood with proximal and distal muscle weakness predominantly of the lower limbs. Myopathological and neurophysiological findings were indicative of combined neurogenic and myopathic pathology. Early childhood foot deformity was frequent, but no sensory signs were observed. Our findings establish VWA1 as a new disease gene confidently implicated in this autosomal recessive neuromyopathic condition presenting with child-/adult-onset muscle weakness as a key clinical feature.